Investigating Porous Media for Relief Printing Using Micro‐Architected Materials. Issue 11 (12th July 2020) - Gallegos, Michael A.; Garcia, Chelsea M.; Schunk, Peter Randall; White, Benjamin C.; Boyce, Brad L.; Secor, Ethan B.; Kaehr, Bryan
Abstract : Advances in printed electronics are predicated on the integration of sophisticated printing technologies with functional materials. Although scalable manufacturing methods, such as letterpress and flexographic printing, have significant history in graphic arts printing, functional applications require sophisticated control and understanding of nanoscale transfer of fluid inks. Herein, a versatile platform is introduced to study and engineer printing forms, exploiting a microscale additive manufacturing process to design micro‐architected materials with controllable porosity and deformation. Building on this technology, controlled ink transfer for submicron functional films is demonstrated. The design freedom and high‐resolution 3D control afforded by this method provide a rich framework for studying mechanics of fluid transfer for advanced manufacturing processes. Abstract : Three‐dimensionally micro‐architected printing media enable controlled ink transfer in relief printing of functional materials. Design and fabrication of complex printing forms using multiphoton lithography provides a versatile platform to tailor print form–ink–substrate interactions for advanced contact printing. Consistent submicron film thickness using porous printing media is demonstrated, with more complex structures allowing sophisticated control of fluid transfer.